Ancient Rome - Purdy, Susan; Sandak, Cass R. (A civilization project book., 1982)
Briefly traces the development of Roman civilization and gives instructions for making models of such Roman artifacts as armor, mosaics, arches, togas, coins, a battering ram, and an assault tower.